Bayt al-Hikmah - House of Wisdom. The future of Islam and Muslims in Iceland Identity Construction and Solidarity through Interculturalism, Communicative Dialogue and Mutual Understanding - Halldór Nikulás Lár 1954- (2021)
The ‘othering’ of Muslims is a growing problem in Europe, as an ethnic construct is now placing all Muslims in one homogeneous group of people. This study shows that the Jihadist interpretation of Islam, with its consequential actions, is the main reason for this social demarcation of Muslims. Therein lies the problem, not in Islam itself as a religion, but a particular type of interpretation and reaction. Everything points to the fact that this extremist interpretation is far from being an accurate representation of Islam. The problems in the European-Muslim relationship are not true for Iceland, but this gradual change should be a lesson to learn from. The empirical data confirms that this does not have to be a problem. Problematic Muslim integration into Europe is due to a) a stereotypical demarcation of Muslims, b) the lack of understanding and the inability of multiculturalism to cope with Muslim spirituality and desire for religious life in a secularistic society. Thus, Europe is now looking to interculturalism for help. Two things are imperative to prevent or diminish the likelihood of this EuropeanMuslim friction entering Icelandic reality: 1) An understanding of Islam as a religion and the current ideological reformation within the Muslim ummah. The Qur’an and Islam are not the problems in Western societies. Islam as a religion has no inherent anti-social, antipluralistic, anti-human rights, or anti-Western elements built into it, and any such claim is to be found in the mind of the interpreter, as taken out of both historical and societal context. 2) Iceland needs to make certain provisions in its integration policies by including interculturalism. The deepening of various diversity in Iceland calls for a reevaluation of the existing diversity management policy to better facilitate solidarity and a sense of belonging. Such elements are considered in political philosophy to be imperative for the cultural meetings of diverse groups.